The oath of office as public value guardian - Rutgers, Mark R. (2010)
The oath of office is perhaps the ultimate means to set public office apart: Public functionaries in most countries have to swear to let public interests prevail over private concerns. This seems at odds with the prevailing liberal/managerial idea that public and private employment is not distinct at all. The oath of office establishes a moral commitment to the office that transcends a contractual, managerial, and/or legal approach to public authority. It signifies the guardianship of public officers and links personal conscience with public values and public interests. This article concludes that we should guard against using an oath of office as a remedy against increased reliance on private interests and mo tivations; rather the latter may endanger a public service ethics and annul any meaning and function an oath may still represent to begin with. - Reproduced.
Keywords: Public administration